Avoidable Hospitalization Trends From Ambulatory Care-Sensitive Conditions in the Public Health System in México - Ofelia Poblano Verástegui; Laura del Pilar Torres-Arreola; Sergio Flores-Hernández; Armando Nevarez Sida; Pedro J. Saturno Hernández (Frontiers Media S.A., 2022)
ObjectivesTo estimate and identify the variations in rates of Avoidable Hospitalization for Ambulatory Care Sensitive Conditions (AH-ACSC) in public institutions of the Mexican health system during the period 2010-2017.MethodsSecondary analysis of the hospital discharge database of the Ministry of Health (MoH) from 2010 to 2017. AH for ACSC was calculated by age group and sex per 100,000. Variations per year between institutions were calculated with the extreme quotient (EQ), coefficient of variation (CV) and systematic component of variance (SCV). Adjusted AH rates were calculated by group of causes (acute, chronic and preventable by vaccination). Adjusted AH trend rates were analyzed by Join Point Regression.ResultsFor the period 2010-2017, the number of AH for ACSC decreased from 676,705 to 612,897, going from almost 13% to 10.7% of hospital discharges. There is consistency in terms of relative variance magnitude. But, with regards to SCV, the change remained constant, and in a second period of 2015-2017, high variation was observed by SCV ≥ 3. All-cause AH is diminishing in all institutions. AH rates for diabetes are the highest, but like other chronic diseases, there was a decline in the period from 2010 to 2017. The relative reduction varied from 15% for heart failure to 38% for complications from diabetes or hypertension, to 75% for angina.ConclusionsAH for ACSC is an indirect indicator of quality and access to first-level care. Variations by institutions are observed. This variation in CV and SCV across subsystems and states may be due to inequities in the provision of services. The factors that contribute to the burden of AH for ACSC in the Mexican Health System require detailed analysis.